Interventricular and intra-left ventricular electromechanical delays in right ventricular paced patients with heart failure: implications for upgrading to biventricular stimulation. Issue 12 (14th November 2003) - Bordachar, P; Garrigue, S; Lafitte, S; Reuter, S; Jaïs, P; Haïssaguerre, M; Clementy, J
Abstract : Objective: To correlate, in patients with right ventricular pacing (RVP), the QRS width with electromechanical variables assessed by pulsed Doppler tissue imaging echocardiography. Secondly, to find reliable parameters for selecting RVP patients who would respond to biventricular pacing (BVP). Methods: 26 randomly selected control patients with RVP (mean (SD) ejection fraction 74 (3)%) (group A) were matched on sex and age criteria with 16 RVP patients with drug resistant heart failure (mean (SD) ejection fraction 27 (5)%) (group B). All patients were pacemaker dependent and all underwent pulsed Doppler tissue imaging echocardiography. This technique provided the intra-left ventricular (LV) electromechanical delay and the interventricular electromechanical delay. The Gaussian curve properties of data from group A patients provided the normal range of ECG and echographic parameters. Design: Prospective study. Setting: University hospital (tertiary referral centre). Results: Data from the control group showed that an interventricular electromechanical delay or an intra-LV electromechanical delay > 50 ms would identify patients with a significantly abnormal ventricular mechanical asynchrony (p < 0.05). In the same manner, a QRS width > 190 ms was considered significantly larger in group B patients (p < 0.05) than in controls. In Group B patients, there was no correlation between the QRS width and the interventricular electromechanical delay ( r  =  −0.23, NS) or the intra-LV electromechanical delay ( r  =  0.19, NS). Seven group B patients (44%) were misclassified by ECG criteria for ventricular mechanical asynchrony identification: four patients (25%) had a QRS width similar to that of controls but with a significantly prolonged intra-LV electromechanical delay and interventricular electromechanical delay; and three patients (19%) had a QRS width significantly larger than that in controls but without significant ventricular mechanical asynchrony. Conclusions: The QRS width is not a reliable tool to identify RVP patients with ventricular mechanical asynchrony. In RVP patients, an interventricular electromechanical delay or intra-LV electromechanical delay > 50 ms reflects a significant ventricular mechanical asynchrony and should be required to select patients for upgrading to BVP.